2017
DOI: 10.15407/ubj89.01.038
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IRE1 modifies hypoxic regulation of G6PD, GPI, TKT, TALDO1, PGLS and RPIA genes expression in U87 glioma cells

Abstract: We have studied the effect of hypoxia on the expression level of mRNA of the basic enzymes of pentosephosphate cycle (G6PD, TKT, TALDO1,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
(67 reference statements)
0
2
0
Order By: Relevance
“…Evidence has indicated that changes to the microenvironment resulting from hypoxia, which is insufficient to maintain cellular function, were associated with cancer pathology. In glioma cells, hypoxia decreased the gene expression of NCOA1 (55). It is known that Helicobacter pylori is responsible for gastric inflammation and gastric malignancy, which causes general inflammatory stress within the gastric mucosa, activating multiple oncogenic pathways and inducing epigenetic alterations, including histone modifications (56).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…Evidence has indicated that changes to the microenvironment resulting from hypoxia, which is insufficient to maintain cellular function, were associated with cancer pathology. In glioma cells, hypoxia decreased the gene expression of NCOA1 (55). It is known that Helicobacter pylori is responsible for gastric inflammation and gastric malignancy, which causes general inflammatory stress within the gastric mucosa, activating multiple oncogenic pathways and inducing epigenetic alterations, including histone modifications (56).…”
Section: Univariate Analysis Multivariate Analysis ------------------mentioning
confidence: 99%
“…It has been shown that the expression of G6PD in tumor cells is higher compared with that in normal cells, and its expression is associated with the overall survival of tumor patients (2,5). Numerous studies have also demonstrated increased G6PD activity in several types of cancer, including bladder cancer, carcinoma of the endometrium, prostate cancer, kidney cancer, stomach cancer, cholangiocarcinoma, colon adenocarcinoma, lung cancer, cervical cancer, carcinoma of the ovary, hepatocellular carcinoma (HCC), glioma, pancreatic cancer and melanoma (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Based on the findings of previous studies, the aim of the present review was to focus on the mechanism underlying the role of G6PD in tumorigenesis and tumor development, as G6PD is hypothesized to become a topic of increased interest with regards to cancer in the future.…”
Section: Introductionmentioning
confidence: 99%